CO2 Energy Reactor – Integrated Mineral Carbonation: Perspectives on Lab-Scale Investigation and Products Valorization - Santos, Rafael M.; Knops, Pol C. M.; Rijnsburger, Keesjan L.; Chiang, Yi Wai (Frontiers in Energy Research, 2016)
To overcome the challenges of mineral CO2 sequestration, Innovation Concepts B.V. is developing a unique proprietary Gravity Pressure Vessel (GPV) reactor technology, and has focussed on generating reaction products of high economic value. The GPV provides intense process conditions through hydrostatic pressurization and heat exchange integration that harvests exothermic reaction energy, thereby reducing energy demand of conventional reactor designs, in addition to offering other benefits. In this paper, a perspective on the status of this technology and outlook for the future is provided. To date, laboratory-scale tests of the envisioned process have been performed in a tubular “rocking autoclave” reactor. The mineral of choice has been olivine (~Mg1.6Fe2+0.4(SiO4) + ppm Ni/Cr), although asbestos, steel slags and oil shale residues are also under investigation. The effect of several process parameters on reaction extent and product properties have been tested: CO2 pressure, temperature, residence time, additives (buffers, lixiviants, chelators, oxidizers), solids loading, and mixing rate. The products (carbonates, amorphous silica and chromite) have been physically separated (based on size, density and magnetic properties), characterized (for chemistry, mineralogy and morphology) and tested in intended applications (as pozzolanic carbon-negative building material). Economically, it is found that product value is the main driver for mineral carbonation, rather than, or in addition to, the sequestered CO2. The approach of using a GPV and focusing on valuable reaction products could thus make CO2 mineralization a feasible and sustainable industrial process.